Sergileme mekânlarının aydınlatılması ve yapı kredi kültür sanat binasının incelenmesi - Özgür, Pınar Ceren (My University, 2020)
Sergi; halkın gezip görmesi, tanıması için uygun biçimde yerleştirilmiş ürünlerin, sanat eserlerinin tümü olarak tanımlanmaktadır. Müze ve sergi mekânları, sanat eserlerinin sürekli ya da geçici bir zaman diliminde sergilenmesini ya da korunmasını amaçlar. Sergileme mekânlarının aydınlatılması, hem sergilenen nesnelerin ziyaretçi tarafından algılanmasını kolaylaştırmayı hedeflemektedir. Ayrıca bu tasarım, eserin ışıktan zarar görmesini önlenmeye de yöneliktir. Sergileme mekânları aydınlatılırken mekânın özellikleri, sergilenecek eserin özellikleri, kullanıcının özelliklerinin değerlendirilmesi ve en makul tasarımın uygulanması gerekmektedir. Yapılan bu tez çalışmasında birinci bölüm giriş bölümüdür. Bu bölümde çalışmanın amacı ve kapsamı belirlenmiştir. İkinci bölümde sergi kavramı ve sergi mekânlarının günümüze kadarki gelişim süreci üzerine bilgi verilmiştir. Ayrıca bu bölümde, sergi mekânlarının sınıflandırılması konusunda bilgi verilip yakın zamanda ziyaretçiye açılan sergi ve müze mekânlarından örnekler incelenmiştir. Üçüncü bölümde sergileme mekânlarında aydınlatmanın önemi ve temel ilkeleri hakkında literatür çalışması yapılmıştır. Sergileme mekânlarındaki ziyaretçinin görsel konfor koşulları ve sergilenen eserlerin zararlı ışıktan korunması konusunda araştırma yapılmıştır. Dördüncü bölümde sergi mekânlarının iç mekân aydınlatması; doğal aydınlatma ve yapma aydınlatma olarak incelenmiştir. Doğal aydınlatmaya bağlı gelişebilecek sorunları engelleme amaçlı kullanılabilecek güneş kontrolü hakkında da bilgiler verilmiştir. Beşinci bölümde örnek sergi mekânı olarak Yapı Kredi Kültür Sanat yapısı ele alınmıştır. Yapıda bulunan Galeri 1 mekânında bulunan nesne aydınlatması ve mekân aydınlatması ayrı ayrı incelenmiştir. Yapı Kredi Kültür Sanat Binası incelenirken gözlem ve simülasyon çalışmaları kullanılmıştır. Bu bölümde ek olarak, Yapı Kredi Kültür Sanat binası Galeri 1 mekânı aydınlatma standartları açısından incelenip standartlara uygun olmayan bölümler için iyileştirme önerleri yapılmıştır. Bu çalışmalar sonucunda, sergilenen nesne çeşidi, sergilenme biçimi ve mekânın mimari özelliklerinin aydınlatma tasarımı ile ilişkisi değerlendirilmiştir.

Exhibition; it is defined as complete work of arts and artifacts which are appropriately placed for public visit and recognition. The aim of the museums and exhibition areas are to ensure the protection and exhibition of work of arts either permanently or temporarily. The first exhibition experience is thought to have started with Cabinet of Curiosities. The word cabinet refers to a room that is more than a piece of furniture. The curiosity rooms, which spread rapidly in Europe in the late sixteenth century, consist of a collection of extraordinary objects. In these curiosity rooms in addition to materials and discoveries from the fields of history, archaeology and geology, antique objects were also exhibited. The underlying principle in the creation of rooms is the similarity of objects and materials. These objects are organized into flexible categories. This curiosity continued in the seventeenth century. Following the development of trade networks and the display of objects brought from the Far East through colonization, miniature museums grew and led to the creation of today's exhibition and museum concept. In the eighteenth century, the concept of area became more prominent in exhibition. The exhibition areas were transformed into rectangular planned, roof-lit volumes where all of the walls were used. Natural lighting attracted attention. In the nineteenth century, belief in progress and growing knowledge brought about industrialization. Museums became places where people exchanged cultural information. However, for the first time, artificial lighting was used by Captain Francis Fowke in the Sheepshanks Gallery of Victoria & Albert. The aim was to ensure that people who work long hours during the day as a result of increasing work hours could also come to museums. Designed by architect and engineer Francis Fowke (18231865), the gallery opened on 22 June 1857 and was praised by the press as 'the first public gallery which is perfectly illuminated in daylight and gas light'. Although there was no new broad vision for museum and area use until 1959, this changed with the completion of Frank Lloyd Wright's Guggenheim Museum in New York City. With it's verticality and expanding structure, the building breaks with traditional geometry and brings a different approach to museum design. In the twentieth century, the museum area had its own unique meaning. In the 1960s, new trends in architecture led to the development of the museum as a kinetic, dynamic machine. The introduction of a mobile skeletal structure provides the flexibility of use, as in the design of Renzo Piano and Richard Rogers at the Pompidou Center in Paris. Throughout history, the effect of the concept of exhibition on area varies, while light always acts as a modulating and emphasizing experience factor that supports the effective presentation of the audience. Light creates different and powerful visual experiences in each exhibition. Without light, the impression of area and the enjoyment of art is not possible. Lighting can be used in exhibition areas in different ways depending on the design and usage during area editing. Understanding and structuring lighting in exhibition halls depends on many planning parameters. These parameters and targets for illumination of exhibition areas were determined by the International Illuminating Engineering Society (IES) in 2017 with the IES Report. These parameters, as determined by the IES report, also include the building architecture in which the lighting should match. These include room measurements, interior design, color scheme, available daylight and the nature of the exhibition. Another important parameter is how light and shadow shape the ambiance. The lighting of the exhibition areas is a combination of both facilitating the perception of the exhibited objects by the visitor and providing the visual comfort for the visitor. When the exhibition areas are lightened, the characteristics of the area, the characteristics of the work to be exhibited and the user's characteristics should be evaluated. As a result the most reasonable design should be applied. The focus of the exhibitions -whether art, technology, history – what really matters is to create an attractive, interesting and an exciting presentation. This is where light comes into play: it creates visual experiences in each exhibition, acts as a modulating and emphasizing experience factor, and supports audience-efficient presentation. Visual ambiance should not be tired. It should stimulate but should not create confusion. In larger areas, this requires a differentiated interior design. Without light, the impression of space and the enjoyment of art is not possible. Different light colors, the shape of the light distribution, the design and arrangement of luminaries and light carriers create different light states (light fields) that meet the relevant exhibition requirements. Special attention should be paid to the location of the object: light protection should play an important role in all exhibition areas. Understanding and structuring lighting in exhibition halls depends on many planning parameters. This includes, in particular, the architecture of the building where lighting needs to adapt. These include room measurements, interior design, color scheme, available daylight and the nature of the exhibition. What is of paramount importance is how light and shadow shape the ambiance. In this thesis, the basic principles of lighting of exhibition areas have been examined and in accordance with these objectives, the lighting design of Yapı Kredi Culture and Art Building has been evaluated and suggestions have been developed for the building. The first part of this thesis is the introduction. In this section, the purpose and scope of the study are specified. In the second part, the concept of the exhibition and the development process of the exhibition areas until today are presented. In addition, in this section, information on the classification of exhibition areas and the examples of exhibitions and museums which are recently opened to visitors are investigated. In the third part, a literature review is conducted regarding the importance and basic principles of lighting in exhibition areas. Visual comfort conditions of the visitors in the exhibition areas and the protection of the displayed works from harmful light were researched. In the fourth part, the interior ligthing of exhibition areas is examined as natural lighting and artificial lighting. Information about the solar control that can be used to prevent problems caused by natural lighting is also given. In the fifth part, Yapı Kredi Culture and Art Center is considered as a sample exhibition area. The existing object lighting and space lighting in Gallery 1 in the building were examined separately. One of the exhibitions examined was Sabahattin Ali's "He Could not Get Used to the Cities: Sabahattin Ali's Cities" exhibition between 14 February and 27 April 2018. Another exhibition is "Abracadabra" by Halil Altındere between 12 September and 3 November 2019. In "He Could not Get Used to the Cities: Sabahattin Ali's Cities" exhibition, paintings, showcases and 3D works, personal belongings used by Sabahattin Ali, handwritten texts and photographs taken by Ali in the high-ceiling exhibition area and on the mezzanine connected to this are were displayed to visitors. Altındere, on the other hand, has designed the artist as a magician, his works as magic material and the exhibition area as a stage. He exhibited threedimensional works. It has been observed that as the objects change due to temporary exhibitions in the exhibition area, the number position and location of the routable devices used in the area also change. The last exhibition examined in Gallery 1 is in the Once Upon a Time in Taurus: Sagalassos exhibition held between 27 November and 28 November 2020. Sagalassos (Burdur) and Pisidia Region (the whole of the province of Isparta) such as terracotta figures, statues of gods, goddesses and heroes reflecting the daily and social lives of the Sagalassos people, rituals of belief, stone tools, ornaments, cooking and food bowls. , Afyonkarahisar, Burdur, Antalya, and some of the provinces in Konya.) The works of different periods can be examined in chronological and thematic sections spanning three floors of the buildıng. In addition to this section, high ceiling display area is examined in terms of lighting standards and improvement suggestions are made for the parts that do not comply with the standards. Observation and simulation studies were applied in the exhibition area. Simulations were performed in DIALUX program. Simulation of the existing system was modeled and deficiencies were determined. Based on these results, improvement methods have been developed. Final remarks and recommendations are given in the conclusion part of this research.
Lighting in exhibition areas and examination of yapi kredi kultur sanat building
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: aydınlanma; enlightenment; doğal ışık; natural light; gün ışığı; güneş ışığı; yapay aydınlatma